A possible interplay between HR‐HPV and stemness in tumor development: an in vivo investigation of CD133 as a putative marker of cancer stem cell in HPV18‐infected KB cell line. Issue 12 (12th October 2020) - de Maria, Salvatore; Santoro, Angela; Fuggetta, Maria Pia; Rocchetti, Romina; Cottarelli, Andrea; Lanzilli, Giulia; Stiuso, Paola; Angelico, Giuseppe; Spadola, Saveria; Franco Zannoni, Gian; Rubini, Corrado; Emanuelli, Monica; et al.
Abstract : High‐risk HPVs (HR‐HPVs) are DNA viruses considered as primary etiologic factors in malignancies of the low female genital tract. Their presence has also been documented in oropharyngeal and laryngeal cancers. However, HPV infection is considered a necessary but not sufficient cause of tumoral development; meantime, increasing evidences on the tumorigenic role of cancer stem cells (CSCs) have been documented in the literature. CSCs represent a small subpopulation of neoplastic cells with self‐renewal potential, capable of maintaining tumor growth and cell differentiation, also involved in metastatic process, recurrence, and resistance to chemotherapeutic agents. In the present study, performed on KB cell lines, we evaluated the tumor forming potential of CSCs, and their relationship with the HPV infection status. We started our study by identifying the most aggressive cell line on the minimal number of cells being able of growth in vivo in a model of athymic nude mice (BALB/c nu/nu). We used an oral‐derived KB cell line separated in the KB‐CD133+ and KB‐CD133‐ populations, by using immunomagnetic beads and fluorescence‐activated cell sorting (FACS). The separated populations were injected in athymic nude mice (BALB/c nu/nu). Xenograft tumors have been analyzed for tumor size, CD133 expression by immunohistochemistry (IHC) and for DNA HR‐HPV integration by in situ hybridization (ISH), comparing CD133‐enriched xenograft tumors versus the CD133 non‐enriched ones. On standard conditions, the KB cell line has a poor population of glycosylated CD133 marker (<5.0%) when investigated with antibodies versus CD133, and more specifically its glycosylated epitope (AC133). Enriched CD133 KB cells possess a higher capacity of tumor growth in xenograft models of nude mice when compared to KB CD133‐negative cells. We observed that the AC133 epitope, extensively used to purifying hematopoietic stem cells, is able to select an epithelial subpopulation of cancer stem cells with aggressive behavior. We retain that CD133 may be a useful target in anticancer strategies including pharmacological and immunological therapies.